On the mobility-lifetime products in photorefractive GaAs-AlGaAs quantum wells structures determined by moving grating technique measurements - Wichtowski, Marek; Weinert-Rączka, Ewa; Miśkiewicz, Eliza; Branecka, Agnieszka (Photonics Letters of Poland, 2014)
The method to determine mobility-lifetime products of photoexcited electrons and holes in semi-insulating GaAs-AlGaAs quantum wells structures is proposed. The method is based on measurements of a photoconductivity and optical investigations of a photorefractive material response in wave-mixing setup using the running grating technique. Full Text: PDF References L. Solymar, D.J. Webb, A. Grunnet-Jepsen, The physics and applications of photorefractive materials (Clarendon Press: Oxford 1996). D.D. Nolte, M.R. Melloch, Photorefractive effects and Materials, ed. by D.D.Nolte (Kluwer, Dordrecht, 1995). S. Balasubramanian, I. Lahiri, Y. Ding, M.R. Melloch, D.D. Nolte, "Two-wave-mixing dynamics and nonlinear hot-electron transport in transverse-geometry photorefractive quantum wells studied by moving gratings", Appl. Phys. B 68, 863 (1999). CrossRef M Wichtowski, "Wave mixing analysis in photorefractive quantum wells in the Franz–Keldysh geometry under a moving grating", Appl. Phys. B 115, 505 (2014). CrossRef Q. Wang, R.M. Brubaker, D.D. Nolte, "Photorefractive phase shift induced by hot-electron transport: multiple-quantum-well structures", J. Opt. Soc. Am. B 9, 1773 (1994). CrossRef M. Shur GaAs devices and circuits (Springer, New York, 1989). D.D. Nolte, "Semi-insulating semiconductor heterostructures: Optoelectronic properties and applications", J. Appl. Phys. 85, 6259 (1999). CrossRef G.C. Valley, H. Rajbenbach, H.J. von Bardeleben, "Mobility?lifetime product of photoexcited electrons in GaAs", Appl. Phys. Lett. 56, 364 (1989). CrossRef A. Ziółkowski, "Temporal analysis of solitons in photorefractive semiconductors", J. Opt. 14, 035202 (2012). CrossRef